Answer:
Axis of symmetry:
![x=-\frac{5}{8}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B5%7D%7B8%7D)
Vertex:
![(-\frac{5}{8},-2\frac{9}{16})](https://tex.z-dn.net/?f=%28-%5Cfrac%7B5%7D%7B8%7D%2C-2%5Cfrac%7B9%7D%7B16%7D%29)
Step-by-step explanation:
The given quadratic equation is
![y=4x^2+5x-1](https://tex.z-dn.net/?f=y%3D4x%5E2%2B5x-1)
By comparing to the general quadratic function;
![y=ax^2+bx+c](https://tex.z-dn.net/?f=y%3Dax%5E2%2Bbx%2Bc)
We have a=4,b=5,c=-1
The equation of the axis of symmetry is given by the formula;
![x=-\frac{b}{2a}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7Bb%7D%7B2a%7D)
We got this formula by completing the square on the general quadratic function.
We substitute a=4 and b=5 to obtain;
![x=-\frac{5}{2(4)}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B5%7D%7B2%284%29%7D)
![x=-\frac{5}{8}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B5%7D%7B8%7D)
is the axis of symmetry.
To find the y-value of the vertex, we put
![x=-\frac{5}{8}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B5%7D%7B8%7D)
into the function to obtain;
![y=4(-\frac{5}{8})^2+5(-\frac{5}{8})-1](https://tex.z-dn.net/?f=y%3D4%28-%5Cfrac%7B5%7D%7B8%7D%29%5E2%2B5%28-%5Cfrac%7B5%7D%7B8%7D%29-1)
![y=4(-\frac{5}{8})^2+5(-\frac{5}{8})-1](https://tex.z-dn.net/?f=y%3D4%28-%5Cfrac%7B5%7D%7B8%7D%29%5E2%2B5%28-%5Cfrac%7B5%7D%7B8%7D%29-1)
![y=-\frac{41}{16}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B41%7D%7B16%7D)
The vertex of the given function is